Proposição de uma Arquitetura Baseada na Tecnologia Blockchain para Logística Reversa: Um Estudo em uma Indústria de Painéis de Madeira - Barretti, Jayson Wilson (2024)
Given the environmental crisis resulting from the rampant consumption of natural resources and the lack of material and waste reuse, organizations are taking responsibility for adopting impactful measures to mitigate environmental and societal damage. The convergence of environmental, social, and governance aspects through ESG is essential for promoting sustainable resilience. In this context, the present study proposes a blockchain-based architecture to reintegrate waste into the production process in manufacturing companies. Objectives include identifying and applying blockchain architectures to facilitate this return, aiming to investigate their support for reverse logistics and production planning, creating a secure and decentralized technological ecosystem for real-time data transmission and material tracking, promoting waste reuse, and driving sustainability. The methodology adopted encompasses theoretical research to substantiate the topics addressed, the proposition of the blockchain architecture to enable the return of materials to manufacturing, and its conceptual application in a reconstituted wood panel industry. The delimitation of the work is based on theoretical research and a systematic literature review, establishing criteria for content analysis and reporting of results in the proposal of a conceptual architecture and its theoretical exemplification of application in the cited industry. Specialized literature highlights blockchain as advantageous for participants in reverse supply chains; however, there are no studies on its application in manufacturing, especially through reverse logistics. This research concludes the relevance of blockchain technology for sustainable supply chain management, offering valuable insights to science by exploring its traceability and transparency capabilities. The implications of promoting sustainable practices and reducing natural resource consumption can foster more sustainable societies. In the meantime, integrating blockchain with other emerging technologies offers opportunities to redesign processes, increase efficiency, and adopt more sustainable business models for managers and organizations.